Can environmental regulations and R&D subsidies promote GTFP in pharmaceutical industry? Evidence from Chinese provincial panel data - Yang, Yue-Di (Frontiers in Public Health, 2022)
Based on the panel data of 30 provinces in China's pharmaceutical industry from 2000 to 2019, this paper proposes to combine the super efficiency SBM model and GML productivity index to calculate the static and dynamic green total factor productivity (GTFP). Then, the Tobit model is adopted for regression analysis on how environmental regulations, government R&D subsidies, and their cross-terms affect the GTFP. Findings suggest that: (1) Static analysis reveals that the GTFP in China's pharmaceutical industry is markedly different among provinces and regions, and the dynamic analysis shows an upward trend from 2000 to 2019. (2) The GTFP of the pharmaceutical industry and environmental rules are connected in a U-shape. The government R&D subsidies to GTFP are positive and significant, and with the expansion of government R&D subsidies, the promotion effect of environmental regulations on GTFP is enhanced. Therefore, it is necessary to set up differentiated environmental regulations systems in different provinces and increase R&D subsidies to promote the pharmaceutical industry's green development.